ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP LOYALITAS PELANGGAN BELFOODS DI PANGKALPINANG - Candra, Ricki; Astuti, Nelly; Panjaitan, Fery (Jurnal Progresif Manajemen Bisnis, 2022)
This paper has been prepared by Ricki Candra, Student Identity Number 230150095, titled in Indonesian: "Analysis of The Effect of Product Quality, Price, and Promotion on Belfoods Customer Loyalty in Pangkalpinang". This research was conducted by coaching the data in October 2021 until February 2022, and this research was conducted in the territory of indonesia. This thesis consists of 65 pages without attachment. The purpose of this study was to find out the extent to which the influence of free variables, namely product quality, price and promotion influences the variables i.e. Customer loyalty. The study was conducted using primary data analysis, data collection through questionnaires, validity tests, reliability tests, data normality tests, multicollinearity tests, heteroskedasticity tests, multiple linear regression analysis, coefficients of determination, t tests, f tests. Processing statistical data using SPSS 28.0.1.0. Data processing results show simultaneously that product quality, price, and promotion significantly affect customer loyalty levels in Pangkalpinang. Product quality, price, and promotion have a simultaneous effect on customer loyalty. Product quality has a positive and significant effect on customer loyalty. Where if there is an increase in product quality by 1% it will increase customer loyalty by 0.005%. Price has a positive and significant effect on customer loyalty. Where if there is a price decrease of 1% it will increase customer loyalty by 0.454%. Promotions have a negative and significant effect on customer loyalty. Where if there is a decrease in promotions by 1% it will increase customer loyalty by 0.097%.